2017
DOI: 10.1111/jfpp.13344
|View full text |Cite
|
Sign up to set email alerts
|

Separation, purification of anthocyanin and vitis linn polysaccharide from grape juice by the two-step extraction and dialysis

Abstract: Liquid liquid extraction, as a clean and green process, has a great potential in technology and innovation, which has been widely used in industrial production. In this paper, a liquid-liquid extraction process based on L44-NaH 2 PO 4 ATPS was studied for separation and purification of anthocyanin and vitis linn polysaccharide from the grape juice. The concentrations of L44 and NaH 2 PO 4 , temperature and pH as factors of effect on the extraction rates were discussed. Under the optimal conditions, the extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This result suggests that anthocyanins migrated preferentially to the alcohol-rich phase when salt and alcohol concentrations in the system were increased. Higher affinity for the top phase has been observed for the extraction and purification of Dacrydes peel anthocyanins in ATPS composed of ethanol and ammonium sulfate/dipotassium phosphate/potassium dihydrogen phosphate (Al-Alawi et al, 2018) as well as for the extraction and pre-purification of grape juice anthocyanins in ethanol/sodium phosphate ATPS (Tang et al, 2018). Liu et al (2013) also observed an increase in the partition coefficient of purple sweet potato anthocyanins in ethanol/ammonium sulfate ATPS when salt concentration was increased.…”
Section: Anthocyanins Partition In Ethanol/ammonium Sulfate Atpsmentioning
confidence: 99%
“…This result suggests that anthocyanins migrated preferentially to the alcohol-rich phase when salt and alcohol concentrations in the system were increased. Higher affinity for the top phase has been observed for the extraction and purification of Dacrydes peel anthocyanins in ATPS composed of ethanol and ammonium sulfate/dipotassium phosphate/potassium dihydrogen phosphate (Al-Alawi et al, 2018) as well as for the extraction and pre-purification of grape juice anthocyanins in ethanol/sodium phosphate ATPS (Tang et al, 2018). Liu et al (2013) also observed an increase in the partition coefficient of purple sweet potato anthocyanins in ethanol/ammonium sulfate ATPS when salt concentration was increased.…”
Section: Anthocyanins Partition In Ethanol/ammonium Sulfate Atpsmentioning
confidence: 99%
“…The dissolved CHRP (10 mg/mL) solution was slowly and uniformly dropped into the cotton DEAE chromatography column, [45] then eluted with 0.6 mol/L NaCl solution at a flow rate of 1 mL/min. The eluent solution was placed in distilled water in a treated dialysis bag for 48 h [46] . The distilled water was changed every 3–4 h. The polysaccharide concentrate in the dialysis bag was then freeze‐dried to obtain the preliminary purified Hippophae rhamnoides polysaccharide, named PHRP.…”
Section: Methodsmentioning
confidence: 99%